An IclR like protein from mycobacteria regulates leuCD operon and induces dormancy-like growth arrest in Mycobacterium smegmatis. (January 2018) - Angara, Rajendra Kumar; Yousuf, Suhail; Gupta, Shailesh Kumar; Ranjan, Akash
Abstract: leuCD operon encodes isopropylmalate isomerase (IPMI), an essential enzyme in leucine biosynthesis. Leucine biosynthesis is one of the essential metabolic pathways for Mycobacterium tuberculosis survival inside the macrophage. In this study, we identified an IclR like transcription regulator, Rv2989 involved in regulation of leuCD expression. Further, we have shown that the Rv2989 binding site overlaps with the promoter region of leuCD, indicating its direct involvement in the regulation of this operon. Ectopic expression of Rv2989 in M. smegmatis induced growth arrest with significantly decreased levels of leuCD transcript. However, supplementation with leucine could not reverse the growth arrest, suggesting the involvement of Rv2989 in the regulation of other essential pathways. Growth-arrested cells were elongated, had lost acid fastness and accumulated lipid droplets similar to a dormancy-like state. In conclusion, the Rv2989 expression has pleiotropic effects on M. smegmatis. It negatively regulates leuCD operon and induces dormancy-like growth arrest.